A.I. Kuprin’s characters’ in «order and chaos» situation - Абабина, Наталья Васильевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In recent decades, researchers are highly interested in the problem of theoretical understanding of changing and reforming of the society as a whole and complex system. This problem became particularly relevant now because of contradictory processes of social evolution, associated with such categories as ‘chaos’ and ‘order’. Intertransitions and struggle between them became the main contradiction in the process of nonlinear system’s self-organization. Synergistic researches of chaos suggest that in the end one should tend not to eradicate it as a negative, but to complete its synthesis with the order and global cooperation. If the system proved to be viable, chaos takes an active part in its ordering. Such ‘retuning’ implies rejection of the past or its correction in accordance with the time and contributes to a more adequate perception of the environment.A.I. Kuprin became acutely aware of oscillatory processes in the end of XIX – early XX centuries. Researchers stated heterogeneity of his creative method, usually inherent in the transitional periods. The order and chaos’s intertransitions also directly affected his characters. The paper defines that not all of them are able to ‘retune’. Being exposed to the dramatic and tragic collision of chaos, they realize that this way leads nowhere, but they cannot find the strength to change it. They protect themselves from the interaction with the outside world and choose the path of opportunists, confined to their mercantile interests. Therefore, they either endlessly go around in circles or return to the starting point of self-organization.